Study of poly(L-lactide) using Fast Scanning Calorimetry - Arbeiter Daniela (De Gruyter, 2020)
Fast scanning calorimetry (FSC) is an effective analytical tool to characterize the thermal properties of polymers. Heating rates up to 100 000 K/s allow studies at time scales inaccessible with conventional calorimeters, whose rates are typically less than about 0.5 K/s. Recent studies have successfully demonstrated methods for obtaining quantitative analysis of thermal properties of polymer samples using chip-based FSC. Therefore very small sample sizes, such as particles or nonwovens, can be characterized. In this study, we investigated the thermal properties of poly(L-lactide) PLLA with FSC compared to the results from standard DSC methods. PLLA specimens were fabricated via solution casting and needle electrospinning. The results suggest a significant influence of heating rates on the melting temperature of PLLA. The results show that different fabrication methods lead to changes in crystallinity and that FSC results are not completely comparable with standard DSC measurements.